2018
DOI: 10.1161/cir.0000000000000562
|View full text |Cite
|
Sign up to set email alerts
|

COSCA (Core Outcome Set for Cardiac Arrest) in Adults: An Advisory Statement From the International Liaison Committee on Resuscitation

Abstract: Cardiac arrest effectiveness trials have traditionally reported outcomes that focus on survival. A lack of consistency in outcome reporting between trials limits the opportunities to pool results for meta-analysis. The COSCA initiative (Core Outcome Set for Cardiac Arrest), a partnership between patients, their partners, clinicians, research scientists, and the International Liaison Committee on Resuscitation, sought to develop a consensus core outcome set for cardiac arrest for effectiveness trials. Core outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
155
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 222 publications
(169 citation statements)
references
References 108 publications
0
155
0
Order By: Relevance
“…We did show in a sensitivity analysis with the studies that reported data for the same follow-up moment that the estimates were very similar to the main analysis. However, a standardized and comprehensive assessment of neurologic and functional outcomes in cardiac arrest research is needed [9]. In spite of these differences, we encountered homogenous results, which suggests that the time of outcome assessment did not signi cantly in uence the results: the neurological outcome and survival seem to remain constant at different follow-up times.…”
Section: Discussionmentioning
confidence: 82%
“…We did show in a sensitivity analysis with the studies that reported data for the same follow-up moment that the estimates were very similar to the main analysis. However, a standardized and comprehensive assessment of neurologic and functional outcomes in cardiac arrest research is needed [9]. In spite of these differences, we encountered homogenous results, which suggests that the time of outcome assessment did not signi cantly in uence the results: the neurological outcome and survival seem to remain constant at different follow-up times.…”
Section: Discussionmentioning
confidence: 82%
“…This should be a key consideration in the design of future studies/trials, as per the recommendations of the recent Core Outcomes in Sudden Cardiac Arrest (COSCA) statement. 53…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the strengths of the CPC include its extensive use, simplicity, and it is a useful surrogate measure of long‐term outcome . Other measure techniques or scores may possess greater predictive characteristics . Due to the several limitations, results of the present study cannot be easily extrapolated to OHCA patients in general.…”
Section: Discussionmentioning
confidence: 94%
“…With the CPC score, we also used a common outcome parameter . However, in a recently published advisory statement from the international liaison committee on resuscitation, the CPC score has been described to have some limitations, ie, ceiling effects and overestimation of function . Therefore, maybe the modified Rankin Scale (mRS) should be preferred to evaluate the neurological function.…”
Section: Discussionmentioning
confidence: 99%